Diagnostic Accuracy of MRCP in the Evaluation of Obstructive Jaundice - Varsha, .; Nisar, Piriha; Sanjna, .; Shoukat, Shaista; Samad, Abdul (Biological and Clinical Sciences Research Journal, 2025)
Obstructive jaundice is a significant clinical condition that requires timely and accurate diagnosis to guide appropriate management. Endoscopic Retrograde Cholangiopancreatography (ERCP) is considered the gold standard but is invasive and associated with potential complications. Magnetic Resonance Cholangiopancreatography (MRCP) offers a non-invasive alternative, and its diagnostic accuracy warrants evaluation. Objective: To determine the diagnostic accuracy of MRCP in diagnosing obstructive jaundice using ERCP as the reference standard. Methods: This prospective observational study was conducted at the Jinnah Postgraduate Medical Centre (JPMC), Karachi, from September 1, 2024, to February 28, 2025, after obtaining ethical approval. A total of 109 patients aged 18 years or older, of either gender, presenting with clinical features of obstructive jaundice, including jaundice, pruritus, dark-colored urine, and pale stools, were enrolled through non-probability sampling. Patients with contraindications to MRCP or a history of prior biliary surgery were excluded. MRCP findings were compared with ERCP to evaluate diagnostic accuracy. Receiver Operating Characteristic (ROC) curve analysis was performed using SPSS Version 25. Results: MRCP demonstrated a sensitivity of 86.4% and specificity of 88% in diagnosing obstructive jaundice when compared with ERCP. ROC curve analysis revealed an area under the curve (AUC) of 0.864, with a statistically significant p-value (<0.001), indicating strong diagnostic performance. Conclusion: MRCP demonstrates high diagnostic accuracy in detecting obstructive jaundice and can serve as a reliable, non-invasive alternative to ERCP, particularly in the initial diagnostic evaluation or in patients where ERCP is contraindicated.